Self-Definitions and a Whole Identity. Formation of Self-Definitions in Specific Domains Leads in the Postmodern Age to a Whole Identity Formation - Mizokami, Shinichi (Studia Psychologica: Theoria et praxis, 2008)
Some researchers on self and identity have contested Erikson’s view of the adolescent identity formation pattern (i.e. the achieved identity) and proposed the postmodern identity instead. The problem, however, is that the two theories have not been integrated into a general theory of adolescent identity formation in the postmodern age. Although Schachter integrated them through his idea of the "identity configuration", he paid too much attention to the configuration itself, and therefore the total dynamics in his identity study was eventually centralized dynamics like Erikson’s rather than decentralized dynamics. In this article, I move Schachter’s emphasis back to the level of specific domains. Additionally, I contend that adolescents in the postmodern age took two different positions in their identity formation process on the level of specific domains: "the specific domains position” and “the whole position". Finally, I elaborate on the function of the two different positions on this level with the help of Hermans’ theory of dialogical self.